THE IMPACT OF INTERPERSONAL COMMUNICATION AND ACADEMIC SUPERVISION ON ENHANCING TEACHER PERFORMANCE - Norawati, Suarni; Zulher, Zulher; Mikasi, Mikasi (ITB AAS Indonesia Surakarta, 2025)
Teacher performance is important to ensuring the quality of education. Therefore, it is necessary to know the factors that influence teacher performance. This research aims to investigate how teachers perform by examining interpersonal communication and academic supervision of school principals on teacher performance. The sample study is junior high school teachers in Bukit Batu District, totaling 61 people, and all of them were used as samples. Data was obtained using questionnaires, interviews, and observation. Using multiple linear regression for the analysis method the result reveals interpersonal communication and academic supervision have simultaneously been proven to have a significant effect on teacher performance, noteless that interpersonal communication between teachers and principals is going well but is not yet optimal.Â Interpersonal relationships between colleagues, teachers, and principals can help them cope with their work experiences and reduce the possibility of burnout, and it will have a good impact on achievement and performanceÂ Keywords: Teacher Performance; Interpersonal Communication, Supervision School Principal